Colonoscopy: A Two Year Experience from Western Nepal - Chaudhary, S; Chaudhary, P; Jaiswal, N; Chaurasia, RK (Journal of Universal College of Medical Sciences, 2013)
INTRODUCTION: Colonoscopy remains the gold standard in diagnosing lower gastrointestinal pathologies. Colonoscopy is also helpful in preventing colorectal carcinoma by removing adenomatous polyp, however, colonoscopy is a difficult skill to master. Though Upper GI Endoscopy is widely available, colonoscopy facilities are relatively rare in developing world. In this field, the vast majority of reported data come from developed countries, and data from a developing country like Nepal is relatively scarce. With this background, present study was aimed to see clinical profile of patients presented for colonoscopy at a colonoscopy centre from western Nepal. MATERIAL AND METHODS: It was a cross sectional study which was carried out in Endoscopy Centre, Edmond City Hospital, Butwal, Nepal from 1 October 2010 to 31 September 2012. Study was approved by the hospital authorities. All the patients for colonoscopy at our centre were evaluated as per predesigned Pro-forma. Colonoscopy was done in all the patients under intravenous sedation after bowel preparation. Colonoscopic abnormalities were noted and biopsied if indicated and sent for histopathological examination. RESULTS: Sixty patients underwent colonoscopy in our centre during study period, among them 33 (55%) were male and 27 (45%) were female. The mean age was 45.23 ± 15.30 years (range 1678 years). Procedure was completed in 54 (90%) patients. Altered bowel habit, chronic diarrhoea and bloody diarrhoea were the three most common indications for colonoscopy. Significant lesions were seen in 35 (56.67%) patients. Among the patients with significant lesions anal canal or rectum or sigmoid colon were involved in 34 (97.14%) patients. The most common finding in colonoscopy was nonspecific colitis involving rectum and sigmoid, seen in 8 (13.33%) cases. Other findings include ulcerative colitis 6 (10%), anal fissure 6 (10%), haemorrhoids 5 (8.33%), ca colon 4 (6.67%), colonic polyp 4 (6.67%), ca rectum 1 (1.67%) and solitary rectal ulcer 1 (1.67%) patients. CONCLUSION: In present study altered bowel habit, chronic diarrhoea and bloody diarrhoea were the three most common indications for colonoscopy. Anal canal, rectum, sigmoid colon involvement were seen 97.14% patients. There is an urgent need to strengthen Lower GI Endoscopy facilities in resource poor setting. Flexible sigmoidoscopy may be a cheaper and easier initial screening tool for evaluating colorectal diseases. DOI: http://dx.doi.org/10.3126/jucms.v1i3.8761 Journal of Universal College of Medical Sciences Vol.1(3) 2013: 28-32